Analysis of Water Spinach's Marketing with Organic Fertilizer in Sidokaton Village - M. Nurus Sholikhin; Zulfikar Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the marketing strategy of upland water spinach cultivated using organic fertilizer in Sidokaton Village, Kudu District, Jombang Regency. The research used a descriptive quantitative approach with data collected through observation, interviews, questionnaires, and documentation. The respondents consisted of 46 farmers who cultivate upland water spinach using organic fertilizer. Data analysis was conducted using SWOT analysis supported by Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS), while strategy prioritization was determined using the Quantitative Strategic Planning Matrix (QSPM). The analysis shows that the business's main strengths lie in product quality, efficient production costs, and mastery of cultivation techniques. Meanwhile, key weaknesses include low product shelf life and distribution effectiveness. Externally, business opportunities are supported by increasing consumer awareness of healthy vegetable consumption, local market potential, and marketing partnership opportunities, while the main threats come from price competition and climate change. The SWOT matrix results yielded four alternative strategies: SO, WO, ST, and WT. Based on the QSPM analysis, the SO strategy, which involves optimizing production quality and efficiency to capitalize on market opportunities, achieved the highest Total Attractiveness Score (TAS) of 3.50, making it a priority strategy. The research findings indicate that improving product quality and production efficiency are key factors in enhancing the competitiveness and sustainability of horticultural businesses. This research is expected to inform strategic decision-making in the development of sustainable agribusiness-based agricultural businesses.